Quality control planning to minimize waste at a manufacturing company - Salim, Najib (Universitas Pendidikan Nasional, 2024)
In industrial fields that developed very rapidly, the manufacturing industry was no exception. It was characterized by increasing consumer needs and significant competition between companies. With tight connections between one industry and another, high-quality products or services became a requirement for competitive advantage and a company's need to guarantee business process requirements. In companies, quality control had long been established as an important management strategy to achieve competitive advantage. PT Slamet Langgeng was a manufacturing industry producing candy products. According to existing data, many defects occurred, causing waste in operational costs and affecting the output produced. This paper aimed to analyze the causes of Davos Roll defects and formulate quality control plans so that businesses could be more competitive and able to compete in the global industry. After further review, three types of defects were identified: soft candy, broken candy, and packaging defects. Broken candy had the highest defect rate, reaching 53.89%. These results indicated the need for more intense quality control planning. Problem analysis used a fishbone diagram to determine the root causes, which served as a reference in the process of preparing quality control plans.